International law review on the implementation of the death penalty for foreign citizens involved in drug crimes in Indonesia - Andrey Bekti Sejati; Tiarsen Buaton; Yusak Andri Ende Putra (Goodwood Publishing, 2023)
Purpose: The main focus of this study is to examine the national legal basis used by Indonesia in imposing the death penalty, as well as assessing the suitability of the implementation of this punishment with international legal obligations and standards, especially those related to the protection of human rights. Research Methodology: Using qualitative methods and a normative legal approach, involving the analysis of various legal documents, documented cases, and academic literature. This study also discusses how international law, such as the International Covenant on Civil and Political Rights (ICCPR), and the Vienna Convention on Consular Relations, influences the implementation of the death penalty in Indonesia, especially in cases involving foreign nationals. Results: It also finds that although the implementation of the death penalty for foreign nationals in Indonesia has a strong legal basis in national law, there are several issues and challenges that need to be considered from an international law perspective. Some of these include compliance with fair trial standards, protection of human rights, and diplomatic responses from the convict's country of origin. In addition, international pressure and criticism from human rights organizations highlight the need for a re-evaluation of the death penalty policy, especially in the context of drug cases. Suggestions: Then suggest the need for reform of the death penalty policy in Indonesia by considering a more humane approach and in accordance with international standards.